PENGARUH KONFLIK TERHADAP PRODUKTIVITAS KERJA APARAT DESA DI KECAMATAN ONOHAZUMBA KABUPATEN NIAS SELATAN - Suardi Laia; Yurmanius Waruwu (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The scope of the study aims to determine the effect of conflict on the work productivity of village officials in Onohazumba District, South Nias Regency. The purpose of this study was to see how much influence the conflict had on the work productivity of village officials in Onohazumba District, South Nias Regency.This research uses quantitative research with associative approach. Based on the tcount value of 7,309 and a significant level of 0.000. While the ttable at alpha (α) = 0.05 with a degree of freedom (df) n-k-1 = 32-1-1 = 30 of 1.697. Thus tcount = 7.309 > ttable = 1.697 and the significant level is 0.000 <0.05. So Ha is accepted, H0 is rejected, meaning that the conflict variable (X) has a positive effect on the work productivity of village officials (Y). It was concluded that conflict had a positive influence on the work productivity of village officials in Onohazumba sub-district, South Nias Regency. Based on the results of the study, discussion of research results and conclusions that have been described, it is concluded that conflict has a positive influence on the work productivity of village officials in Onohazumba sub-district, South Nias Regency.